Meningkatkan Semangat Kebangsaan di Sanggar Bimbingan Sungai Buloh Malaysia - Sutarsa, Monika (PT. Riset Press International, 2024)
Education at Sanggar Guidance Sungai Buloh, Malaysia, plays a crucial role in shaping the national spirit and national identity in a society that is rich in history and cultural heritage. Through the application of appropriate knowledge and educational strategies, education at this studio aims to strengthen awareness of national values ​​and develop a sense of pride in local cultural heritage. In this context, community service activities become an important means of strengthening the relationship between education, national identity and community empowerment. Sanggar Guidance Sungai Buloh offers various opportunities for the development of sustainable national education, however challenges such as limited educational accessibility and inequality in education still remain. needs to be addressed. The studio has become an important learning center in its community, with student numbers increasing significantly from 15 to 103. The diverse learning structure and comprehensive curriculum provide opportunities for students to develop holistically. Teachers at the studio have an important role in guiding their students, while the introduction of Indonesian culture strengthens the national spirit. Collaboration with Changemaker Indonesia is a significant step in expanding the influence and impact of service at the Sungai Buloh Guidance Studio. Opportunities are open for the exchange of experience and knowledge between the two countries, giving studio teachers the opportunity to develop their skills. In addition, this collaboration allows for cultural exchange between two different countries, opening up opportunities to enrich the learning experience of students at the studio. It is hoped that, through continued collaboration, the quality of education in the studio can continue to improve and the younger generation can be ready to face future challenges.